The impact of dose rate optimisation and robust optimisation on FLASH proton therapy treatment plan quality and dose rates - Lövgren, Nathalie; Nilsson, Rasmus; Traneus, Erik; Petersson, Kristoffer (Frontiers in Oncology, 2025)
Background and purposeBragg peak FLASH proton therapy (FLASH-PT) relies on fast dose delivery (≥ 40 Gy/s) to elicit a normal tissue sparing effect. FLASH-PT beam delivery modifications lead to inferior margin-based FLASH-PT treatment plan quality compared to intensity modulated proton therapy (IMPT). To achieve ultra-high dose rates to regions of interest, dose rate optimisation may need to be utilised as part of the treatment planning process. This study aims to determine the impact of dose rate optimisation and robust optimisation on FLASH-PT treatment plan quality and achievable dose rates. All FLASH-PT plans are also compared to IMPT plans to determine the clinical applicability of the technique.Materials and methodsFLASH-PT and IMPT treatment plans were generated for bone (n = 3), brain (n = 4) and lung (n = 3) targets for a one-beam-per-fraction and multi-beam-per fraction delivery, respectively. The open-source MIROpt treatment planning system (TPS) was used to generate dose rate optimised FLASH-PT plans, while a research version of the RayStation TPS was used to generate non-dose rate optimised, margin-based, and robust FLASH-PT plans. Dose rate coverage was evaluated for different dose and dose rate thresholds.Results and conclusionDose rate optimised FLASH-PT plans were associated with significantly worse target dose coverage, whilst significantly improving dose rate coverages to organs at risk, compared to non-dose rate optimised plans. The use of dose rate optimisation should be used with caution as it may lead to degraded plan quality. Robust optimisation improved target coverage compared to margin-based plans, without compromising dose rate coverage. FLASH-PT plans struggle to achieve IMPT-equivalent D95% and is associated with non-significant increases in organ at risk doses compared to IMPT, regardless of TPSs and treatment planning techniques (margin and robust). Future work will focus on improving D95%, reducing organ at risk doses, and optimising MU/spot delivery to improve plan quality, while further increasing the dose rates.